Covalently immobilized catalase on functionalized graphene: effect on the activity, immobilization efficiency, and tetramer stability. (31st October 2018) - Barreca, Davide; Neri, Giulia; Scala, Angela; Fazio, Enza; Gentile, Davide; Rescifina, Antonio; Piperno, Anna
Abstract : The different anchorage modes of catalase covalently linked to graphene affect the secondary and quaternary structures determining the biological properties. Abstract : Herein we describe, for the first time, the covalent immobilization of catalase (CAT) on functionalized graphene surfaces (G) by exploiting the azalactone chemistry for the post-functionalization of graphene-based materials. The structure, morphology and chemical composition of catalase immobilized on graphene (CAT-G) have been investigated by Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDX). The biological responses such as catalytic activity, cellular uptake, internalization pathway, and the ability to protect lymphocytes from oxidative stress induced by H2 O2 together with the unforeseen ability to increase the lifetime of the free catalase in solution have been deeply investigated. From our studies, it is evident that the behavior of CAT covalently linked to modified graphene depends on the CAT/G ratio that affects the secondary structure and the tetramer stability of CAT. In order to support the experimental results, we have also investigated the behaviors of two appropriately designed model systems, named CAT-surfer and CAT-skier, by molecular dynamics calculations. These in silico results parallel the experimental results proving our hypothesis that the CAT-surfer maintains the conformational flexibility needed for a biological response, whereas CAT-skier favors the dissociation of the tetramer subunits, involving the inactivation of the enzyme.